PENGARUH KERAGAMAN PRODUK, TATA LETAK PRODUK DAN SUASANA TOKO TERHADAP MINAT BELI ULANG - Lili Salfina, Lili Salfina; Fernando, Reynaldi (Universitas Sumatera Barat, 2023)
Abstract The clothing business in Indonesia is growing following the current of odernization. More and more business people in the field of fashion will result in increasingly fierce competition. This competition makes business people formulate strategies so that the business they are involved in can survive. The Rasky Fashion located in the Balai Baru area faces this situation because of its location or proximity to competitors who offer similar products. In this case, Rasky Fashion also very concerned about the level of sales, which does not increase significantly every year. This study aims to determine the effect of product diversity, product layout, store atmosphere on partial and simultaneous repurchase interest. This type of research is quantitative with multiple linear regression analysis method using primary data, data collection methods are carried out by interviewing and distributing questionnaires. The population of this research is the customer of Rasky Fashion, the determination of the number of samples using the Roscoe technique, obtained as many as 40 respondents with the withdrawal using the purposive sampling method. The results showed that product diversity, product layout and store atmosphere had a significant effect on repurchase interest at Rasky Fashion partially and simultaneously. The regression is Y = 5,435 + 0,369 X1 + 0,261 X2 + 0,302 X3 and the Adjusted R Square value is 0.683, meaning that the independent variable is able to explain the dependent variable by 68.3% while the remaining 31.7% is explained by other variables not examined in this study.